(1318) a model to develop Egyptian agriculture to solve the problem of unemployment and low per capital(1318) income in Egyptian agriculture نموذج لتطوير الزراعة المصرية لحل مشكلة البطالة وانخفاض دخل الفرد (1318) في الزراعة المصرية - arman, I. M. I. (The institute of national planning., 2018)
this paper describes research into an optimization model for Egyptian agriculture using computerized linear programming techniques which could greatly increase labour absorption,whilst requiring very little capital, and could increase aggregate farming profitability.